Pelatihan Meningkatkan Kemampuan Menulis Arab Pegon Bagi Anak Desa Sumbersari Kencong Kepung Kediri - Abdul Mujib; Muhammad Faiz Amiruddin (LP3M IAIFA Kediri, 2020)
The main method of teaching system in Madrasah Islamiah Darussalamah Sumbersari Kencong Kepung Kediri is with the system of teaching and learning according to their respective classes. In this school activity is to learn the procedures of writing Arabic pegon, because it is still in the beginner stage. The goal to be achieved in this research is: to improve the ability to write Arabic pegon santri. To achieve this goal, the authors use the PAR method or Participatory Action Research. With data collection techniques in the form of interviews, observations and documentation. For data analysis using data reduction, data presentation and conclusion withdrawal.